Legal regime regulating the laying and protection of submarine cables in the Republic of Croatia - Jurdana, Irena; Rukavina, Biserka; Tominac Coslovich, Sandra (2021)
One of the strategic development priorities of the Republic of Croatia is the development and construction of a modern telecommunications network and the availability of high-speed Internet throughout its territory, especially in rural areas and on islands. To enable this, it is important to build a reliable and resilient communication infrastructure. With the cooperation of all stakeholders in the construction, from telecom operators to local and state administrations responsible for the maritime demesne, and with efficient legislation, it is possible to achieve sustainable development of submarine cable infrastructure.The paper provides an overview of the legal aspects of submarine optical cable infrastructure design and application at the national and international levels. Special attention is dedicated to the analysis of a national legal regime regulating the protection and sustainable use of submarine cables. Thus, the authors will provide critical analysis of a kind of dualism present in the application of the Ordinance on the Register of Concessions and the Ordinance on the Register of Concessions on the Maritime Demesne and offer suggestions for potential improvements of a national legal framework pertaining to the right of laying and legally protecting submarine cables.
Bibliografija: 26 jed.
Summary.
Keywords: Podmorski optički kablovi -- Optičke komunikacijske mreže -- Morski okoliš -- Zakonske odredbe; Hrvatska